A Convenient Synthesis of α-Substituted β,γ-Unsaturated Ketones and Esters via the Direct Addition of Substituted Allylic Zinc Reagents Prepared by Direct Insertion - Sämann, Christoph; Knochel, Paul (Synthesis, 2013)
A practical and convenient procedure for the synthesis of α-substituted β,γ-unsaturated ketones and esters has been developed. Substituted allylic zinc reagents, prepared via direct metal insertion in substituted allylic halides, react readily with a broad range of acid chlorides and chloroformates furnishing the corresponding α-substituted β,γ-unsaturated ketones and esters in high yield and perfect regioselectivity.
Keywords: organozinc reagents; addition; unsaturated ketones and esters; insertion; allylic halides